Robot Fully Assisted Upper-Limb Functional Movements Against Gravity to Drive Recovery in Chronic Stroke: A Pilot Study - Caimmi, Marco; Giovanzana, Chiara; Gasperini, Giulio; Molteni, Franco; Molinari Tosatti, Lorenzo (Frontiers in Neurology, 2022)
Background Stroke is becoming more and more a disease of chronically disabled patients, and new approaches are needed for better outcomes. An intervention based on robot fully assisted upper-limb functional movements is presented. Objectives To test the immediate and sustained effects of the intervention in reducing impairment in chronic stroke and to preliminarily verify the effects on activity. Methodology Nineteen patients with mild-to-severe impairment underwent 12 40-min rehabilitation sessions, 3 per week, of robot-assisted reaching and hand-to-mouth movements. The primary outcome measure was the Fugl-Meyer Assessment (FMA) at T1, immediately after treatment (n = 19), and at T2, at a 6-month follow-up (n = 10). A subgroup of 11 patients was also administered the Wolf Motor Function Test Time (WMFT TIME) and Functional Ability Scale (WMFT FAS) and Motor Activity Log (MAL) Amount Of Use (AOU), and Quality Of Movement (QOM). Results All patients were compliant with the treatment. There was improvement on the FMA with a mean difference with respect to the baseline of 6.2 points at T1, after intervention (n = 19, 95% CI = 4.6–7.8, p < 0.0002), and 5.9 points at T2 (n = 10, 95% CI = 3.6–8.2, p < 0.005). Significant improvements were found at T1 on the WMFT FAS (n = 11, +0.3/5 points, 95% CI = 0.2–0.4, p < 0.004), on the MAL AOU (n = 11, +0.18/5, 95% CI = 0.07–0.29, p < 0.02), and the MAL QOM (n = 11, +0.14/5, 95% CI = 0.08–0.20, p < 0.02). Conclusions Motor benefits were observed immediately after intervention and at a 6-month follow-up. Reduced impairment would appear to translate to increased activity. Although preliminary, the results are encouraging and lay the foundation for future studies to confirm the findings and define the optimal dose-response curve. Clinical Trial Registration www.ClinicalTrials.gov, identifier: NCT03208634.